Development priority zoning in China and its impact on urban growth management strategy. (February 2017) - Wang, Wei; Zhang, Xiaoling; Wu, Yuzhe; Zhou, Ling; Skitmore, Martin
Abstract: Urban growth management is a popular topic for study area all over the world. Despite the increasingly rich literature, however, little has been considered of the complex relationship between the various urban development factors and their feedback structure. This paper contributes in understanding the mechanism of, and establishing a link between, urban growth management oriented by zoning in China (namely development priority zoning or DPZ). A system dynamics urban growth model is presented that is integrated with China's socio-economic development situation. With Yiwu city and Qingtian County as case studies, the model is applied in simulating urban growth under different driving modes. The results indicate that the DPZ in these two areas has an influence on urban growth management strategy, with the driving mode of urban growth affecting economic development levels, migration and types of land conversion. It is concluded that different driving modes are needed for different types of regions according to the functional positioning of their DPZ and that the model contributes to their identification. Highlights: Relationship between urban development factors and feedback structure is studied. We study the mechanism and establish a link between urban growth management strategies. DPZ in the two case areas has an influence on urban growth management strategy. Different driving modes are needed for different types of regions according to the functional DPZ.